Epidemiological investigation of a pertussis outbreak among schoolchildren in Burkina Faso, 2019 - Ilboudo, Abdoul K.; Cissé, A.; Savadogo, M.; Sana, M.; Gouba, N.; Sourabié, Y.; Nayaga, R.; Tialla, D.; Zongo, M.; Yaméogo, I.; Tarnagda, Z. (BioMed Central, 2025)
Introduction: Pertussis remains among the top ten most common fatal aetiologies of acute respiratory infections worldwide. This study reports findings from the first laboratory-confirmed pertussis outbreak among primary schoolchildren in Burkina Faso.